Analisa Pengaruh Citra Merek (Brand Image) dan Kepercayaan Merek (Brand Trust) Terhadap Loyalitas Merek (Brand Loyalty) ADES PT. Ades Alfindo Putra Setia - Bastian, Danny Alexander (Jurnal Strategi Pemasaran, 2014)
This study aims to explain the variable brand image and brand trust that affect brand loyalty ADES PT. Ades Alfindo Putra Setia. This type of research in this study include causal research, which is a research finding and describing the relationship (cause and effect). The population of retailer ADES PT Ades Alfindo Putra Setia. Data collection techniques using observational methods by distributing questionnaires. Types and sources of data using primary data. The results of this study variables brand image is a significant positive effect on brand loyalty, brand trust affects brand loyalty, brand image and significant effect on brand trust.